Dual Biologic or Small Molecule Therapy in Pediatric Inflammatory Bowel Disease: A Single Center Experience - Cheng Guo; Jin Zhou; Guoli Wang; Jie Wu (Children)
Purpose: Currently, there is no clinical data reported on the therapy of dual biological agents in pediatric-onset inflammatory bowel disease (PIBD) patients in China. The purpose of this study was to evaluate the efficacy and safety of dual biologic therapy or biologics combined with small molecule drugs in refractory PIBD patients in China. Methods: Clinical, laboratory, endoscopic, and ultrasound data of PIBD patients from the Department of Gastroenterology of Beijing Children’s Hospital between January 2021 and October 2024 were retrospectively analyzed. PIBD patients who received dual biologic treatment or a combination of biologic and small molecule therapy were included in this study. Steroid-free clinical remission and adverse events were recorded. Results: In this retrospective study, out of 520 children with IBD, twelve children (2.3%) were diagnosed with refractory PIBD and met the criteria for dual biotherapy, including four with UC (33%) and eight with CD (67%). The median age of patients was 13.64 (range, 1.2–17.1) years at eligibility for dual biologic therapy. There are eight (67%) patients treated with infliximab/ustekinumab (IFX + UST), three (25%) patients with upadacitinib/ustekinumab (UPA + UST), one (8%) patient with infliximab/vedolizumab (IFX + VDZ). At 3, 6, and 12 months of dual biological treatment, 91.2% (11/12), 100% (12/12), and 100% (12/12) patients showed steroid-free clinical remission, respectively. The median fecal calprotectin decreased significantly from 1852.5 µg/g (IQR, 762.5–1988.25) at baseline to 359.0 (IQR, 217.5–730.25) μg/g at 3 months, 113 (IQR, 73.7–256) μg/g at 6 months, and 82.5 (IQR, 40.25–122.25) μg/g at 12 months. Only one CD patient with IFX + UST reported mild elevation of aminotransferase, who recovered after symptomatic treatment. Conclusions: Dual biologic or small molecule therapy may be effective and safe for children with refractory PIBD in China.